Imported malaria in pregnant women experienced in Japan. Issue 8 (August 2017) - Kimura, Mikio; Koga, Michiko; Hasegawa, Chihiro; Mutoh, Yoshikazu; Kato, Yasuyuki; Maruyama, Haruhiko
Abstract: Introduction: With ever-growing global exchanges, the number of travelers, including pregnant women, to the tropics is increasing, which poses a risk of contracting malaria. Although there are several reports on imported malaria in pregnancy from Western countries, those focusing on cases experienced in Japan are very limited. Methods: We searched for cases of malaria in pregnancy in the treatment records submitted to the Research Group on Chemotherapy of Tropical Diseases, Japan, during the period 1993–2016. Literature searches were also conducted using an American and a Japanese search system. Results: Ten cases of malaria in pregnant women were identified, including four cases with Plasmodium falciparum . Of eight evaluable cases, only one practiced malaria chemoprophylaxis. Among the nine evaluable cases, eight resulted in uneventful delivery and one P. falciparum case developed severe hepatic disturbance, disseminated intravascular coagulation, and intrauterine fetal death. After the initial attack, none of the Plasmodium vivax / Plasmodium ovale cases practiced chloroquine prophylaxis until delivery. One P. ovale case received a lower dose regimen of chloroquine as acute-stage therapy. Conclusion: This study demonstrated additional cases of imported malaria in pregnant women to the literature and highlighted various epidemiological, demographic, and clinical characteristics. Some of the clinical issues raised need to be investigated. Due to the paucity of the cases worldwide, sharing information among various countries is indispensable, and international guidelines which are now increasingly recommending the use of artemisinins in pregnant women should be referred.